Bioactive metabolites from cultures of the entomopathogenic fungus Pleurocordyceps ophiocordycipiticola TBRC-BCC 9612 - Siriporn Saepua; Karoon Sadorn; Jittra Kornsakulkarn; Patchanee Auncharoen; Suchada Mongkolsamrit; Donnaya Thanakitpipattana; Chawanee Thongpanchang (RSC Advances, 2026)
and highlight several compounds with promising biological profiles for further pharmacological study.
Keywords: Fungal Biology and Applications; Entomopathogenic Microorganisms in Pest Control; Plant and fungal interactions